Low voltage analog synthesizer of orthogonal signals using current mode techniques - Oliveira, VJS; Oki, N. (Institute of Electrical and Electronics Engineers (IEEE), 2003)
An analog synthesizer of orthogonal signals for digital CMOS technology and 3V supply voltage is presented. The adaptive architecture accomplishes the synthesis of mutually orthogonal signal, such as trigonometric and polynomial basis. Simulation results using 0.35 mu m AMS CMOS process are presented for generation of the cosine and Legendre basis.